Approach to Representation of CRI Integrated Mathematics and Verbal (R-MV) to Analyze Misconception of Momentum and Impuls Materials - I Ketut Mahardika; Zulfi Anggraini; Aris Doyan; I Wayan Sugiartana (Postgraduate, University of Mataram, 2020)
Misconception is a misconception that refers to a concept that is not in accordance with scientific understanding or understanding received by experts in that field. This study aims to identify students' misconceptions in solving momentum and impulse problems through the R-MV approach (mathematical representation and verbal representation) integrated CRI (Certainly of Response Index). This research included in the type of qualitative descriptive analysis research. The subject of the research was tenth-grade students of Jember Regency Senior High School. Data collection techniques in this research use method of observation, tests, and interviews. The data analysis technique used was the mathematical representation approach integrated CRI. Based on the results of the research that has been done, the students' misconceptions percentage in Jember Senior High School of science tenth grade on material momentum and impulse through mathematical representation approach integrated CRI of 20.07% and through verbal representation approach integrated CRI of 32.94%. This is included in the category (Almost Very Confident) for mathematical representation and (Sure) for verbal representation, meaning the value that students get as truthful based on understanding material with correct